Advertisement and the extrinsic cues toward buying attitude: Case of Wardah halal cosmetics - Dara Anggun Puspita Dewi; Guruh Ghifar Zalzalah (Asian Journal of Islamic Management (AJIM), 2019)
Purpose: The aim of this research was to determine the influence of effective advertisement (emotional response and environmental response), extrinsic cues (brand image, packaging, and price) toward the consumer buying attitude, and to analyze the influence of extrinsic cues on consumer buying attitude of Wardah through income as the moderating variable.Methodology: The sample was taken by female university students who used the product of Wardah. The sampling technique used was a non-probability sample that is convenience sampling or accidental sampling. The analytical tool used multiple linear regression analysis with SPSS version 20.Findings: The results of multiple regression analysis showed a positive and significant influence on the effective advertisement (emotional response and environmental response), and extrinsic cues (brand image, packaging, and price) toward the consumer buying attitude, and income was positively moderated the extrinsic cues toward the consumer buying attitude.Originality/Contributions: This is the first study to find out, the researcher focused on female university students in Yogyakarta who were using Wardah cosmetic. There were five parts of questions based on the effectiveness of advertising variables, brand image variables, packaging variables, pricing variables, income variables and buying attitude variables